A study of protozoa distribution in Kuantan coastal areas - Mukai, Yukinori; Azmi, Anis Najiha (2021)
Seed production of marine finfish in Malaysia is still facing problems about the live feed of starter diets. Currently, we use S or SS-type rotifers, which have sizes from 100 to 200μm. Early-stage larvae of some marine finfish species select feed less than 100 μm. Protozoa is a collective term of aquatic microorganism that has been identified to be suitable live feed, as their body sizes are less than 100μm. Protozoa is considered to play an important role in microbial food chains. The objective of this study was to detect the suitable protozoa as the live feed from Kuantan coastal areas. Water samples were collected from three places in Kuantan coastal area, which were Pantai Teluk Cempedak, Pantai Sepat, and Pantai Cherok Paloh. The sample water was cultured in the beakers with nutrients for ten days. Various species protozoa were identified, e.g. Euplotes sp. Oxytricha fallax and Nassula microstoma. The sizes of the cultured protozoa range from 40 to 200µm. Protozoa with size less than 100µm were Euplotes sp., Nassula microstoma, and Colpidium colpoda. These protozoa species will be good candidates for live feeds for the larval rearing of marine finfish